Studies on genetic polymorphism of improved cowpea varieties using Simple Sequence Repeats (SSR) marker - Olasan, O.J.; Omoigui, L.; Oluma, H.A.; Aguoru, C.U.; Deo, D.; Ugbaa, M.S.; Ezugwu, J.; Ekeruo, G.; Dughduh, P.; Iyorkaa, N.; Simon, M.; Okoh, T. (2023)
Background and Objective: Several new varieties are released from breeding programs targeted at solving specific threats to cowpea production in Nigeria. As part of efforts to promote crop improvement, this study was carried out to determine the level of genetic polymorphism and phylogenetic relationship that exists among four selected improved varieties of cowpea (SAMPEA-14, SAMPEA-15, SAMPEA-17 and SAMPEA-18) using ten SSR molecular markers. Materials and Methods: The DNA was extracted from 14 days old seedling using the CTAB method. A total of 10 SSR primers were used in the DNA amplification process on a programmed thermal cycler followed by electrophoresis, visualization and scoring of the banding pattern. Data were analyzed on the Minitab 16.0 software for clustering patterns while the Polymorphic Information Content (PIC) of each primer was calculated. Results: Polymorphic information content (PIC) ranged from 0.619 in RB20 to 0.881 in RB38 primers. The top three markers in PIC values were RB38 (PIC = 0.881), CLM0342 (PIC = 0.873) and RB7 (PIC = 0.866). The mean PIC of the ten primers was 0.884. The genetic similarity index of the dendrogram was very low as SAMPEA-17 showed the lowest similarity coefficients of 18.35 away from other varieties while SAMPEA-15 had similarity coefficients of 33.33. Conclusion: This study has revealed high genetic differences among the four varieties studied. All of the varieties may be used as genetic materials in breeding work to improve local landraces to achieve sustainable cowpea production and food security in Nigeria.